MOS 2010 study guide for Microsoft Word, Excel, PowerPoint, and Outlook. - Lambert, Joan, ....-; Cox, Joyce, 1946- (Washington : Microsoft, 2011)
Demonstrate your expertise with Microsoft Office 2010! This all-in-one guide is designed to help you practice and prepare for the four core Microsoft Office Specialist (MOS) exams. With the MOS 2010 Study Guide, you get full, objective-by-objective coverage for: Exam 77-881: Microsoft Word 2010 Exam 77-882: Microsoft Excel 2010 Exam 77-883: Microsoft PowerPoint 2010 Exam 77-884: Microsoft Outlook 2010 Use the book's easy-to-follow procedures and illustrations to review the essential skills measured by the MOS exams. And you can apply what you've learned hands-on-using the downloadable files for all the book's practice tasks.